Pengaruh Model Pembelajaran Berbasis Proyek dalam Kurikulum Merdeka terhadap Hasil Belajar Pendidikan Agama Islam dan Budi Pekerti Siswa di SDN 02 Pariangan - Fadhilah, Fadhilah; Sulaiman, Sulaiman (YASIN, 2025)
This study is motivated by teaching practices that tend to be monotonous and lack variation in classroom management, which negatively affect student motivation and learning outcomes, particularly in the subject of Islamic Religious and Character Education (PAI and BP). The aim of this research is to describe the implementation of Project Based Learning (PjBL) within the Merdeka Curriculum, analyze the learning outcomes achieved, and examine the influence of the PjBL model on the learning outcomes of sixth-grade students at SDN 02 Pariangan. The research method used was quantitative with a correlational approach, involving a sample of 29 students. The results of simple linear regression analysis show a positive and significant relationship between pre-test and post-test scores (R = 0.807; significance = 0.000). The coefficient of determination (R²) was 0.651, indicating that 65.1% of the variation in students’ post-PjBL learning outcomes was influenced by their initial condition. In addition, the paired samples t-test showed a significant difference between pre-test and post-test scores (mean difference = -3.966; significance = 0.000), with a significant increase in post-test scores. These findings demonstrate that the implementation of PjBL within the Merdeka Curriculum has a positive impact on improving students’ learning outcomes in PAI and BP. The conclusion of this study is that PjBL is effective in enhancing learning achievement, encouraging active engagement, and fostering deeper understanding of the subject matter. The implications of this study suggest the need to adopt contextual and collaborative learning models such as PjBL in PAI and BP instruction at the elementary school level.